Pengaruh Lingkungan Sosial Madrasah Dan Gaya Kepemimpinan Kepala Madrasah Terhadap Motivasi Berprestasi Guru - Azhar, Imam (MADINAH, 2014)
Achievement motivation of teachers is a strength or spirit that encourages teachers to excel. So that teachers have a strong achievement motivation. In addition to the school environment, leadership role is also important for achievement motivation of teachers. In exercising leadership, headmaster needs to use the appropriate leadership strategies so that objectives can be achieved. The population in this research was all teachers totaling 67 teachers. The technique sampling used is a stratified random sampling. To determine the number of samples used Taro Yamane formula in order to obtain 40 teachers. The independent variable of this research is the social environmental school and Leadership Styles of Headmaster, and the achievement motivation of teachers as the dependent variable. Sampling technique used in this research is to use the technique of questionnaires and documentation. The results of hypothesis test using SPSS 16.0 while the findings are as follows: (1) there is a positive and significant correlation between social environmental school with leadership styles of headmaster. This is shown in the results obtained by the analysis of the significance test value t count > t table (9.784 > 2.024) and the P value (0.000 < 0.05). (2) There is a positive and significant influence between social environment schools to the Achievement Motivation of Teachers. This is shown in the results obtained by the analysis of the significance test value t count > t table (2.920 > 2.024) and the P value (0.006 < 0.05), and (3) There is a positive and significant influence between leadership styles of headmaster to the Achievement Motivation of Teachers.This is shown in the results obtained by the analysis of the significance test value t count > t table (3.267>2.024) and the P value (0.002<0.05), (4) There is a positive and significant influence between social environmental school and leadership styles of headmaster together to the achievement motivation of teachers. This is shown in the results obtained by the analysis of the significance test value of F count > F table (5.305 > 3.252) and the P value (0.009 < 0.05).